A synergistic hydrothermal-deep eutectic solvent (DES) pretreatment for rapid fractionation and targeted valorization of hemicelluloses and cellulose from poplar wood. (December 2021) - Ma, Cheng-Ye; Xu, Ling-Hua; Zhang, Chen; Guo, Kai-Ning; Yuan, Tong-Qi; Wen, Jia-Long
Graphical abstract: Highlights: Synergistic hydrothermal-DES pretreatment was developed for fractionation of poplar. The hydrolysate is mainly composed hemicelluloses and their degradation products. The optimal concentration of xylooligosaccharide (XOS) is 5.36 g/L in the hydrolysate. The hydrolysate has homogeneous molecular weights and excellent antioxidant activity. The synergistic process remarkably enhanced the glucose yield from 15.72% to 96.33% Abstract: A synergistic pretreatment that realizing effective fractionation and targeted valorization can guarantee the implementability to future biorefinery scenario. In the present study, a stepwise approach using hydrothermal and deep eutectic solvents (DES) pretreatment was developed to preferentially dissociate hemicelluloses and further remove lignin from poplar, while retaining a cellulose-rich substrate that can be easily digested via enzymatic saccharification to obtain glucose. Results showed that the hydrothermal filtrate is mainly composed of xylooligosaccharide (XOS), monosaccharides, byproducts, and xylan-type hemicelluloses, which have homogenous structures and uniform molecular weights distribution as well as excellent antioxidant activity. Subsequent DES pretreatment further removed the lignin barriers, leading to a remarkable increase in the saccharification efficiency from 15.72% to 96.33% under optimum conditions for enzymatic hydrolysis. In short, the integrated pretreatment is effective for dissociating and chemical conversion of poplar wood, which was reasonable to promote the frontier of highly available biorefinery.